IMPLEMENTATION OF ILLUSTRATION DESIGN IN DIGITAL ADVERTISING MEDIA - Rahmat Hidayat; Afrizal H (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: As humans, we have the ability to process visual data better than other types of data. Therefore, in the continuously evolving digital age, the use of digital illustration media becomes more beneficial and effective in advertising or promoting a product. Through the use of illustrative images, it is hoped to attract more audience attention. Illustrations play a vital role as advertising media in digital product marketing in the era of information technology. Method: The advancement of digital technology is driving a shift in advertising strategies from conventional media to more visual, interactive, and communicative digital media. Digital illustrations are used to creatively convey promotional messages, capture audience attention, and build the visual identity of digital products to make them easily recognizable and understood. By utilizing specific colors, shapes, characters, and visual styles, illustrations can effectively represent the values, functions, and advantages of digital products. Results: Illustrations are considered to have an advantage in explaining complex concepts with results that are more acceptable to readers or consumers, making illustration an effective design element to help reflect and explain the values and character of a product or company. Illustrations serve not only as aesthetic elements in digital product advertising but also as strategic visual communication tools. Optimal utilization of digital illustrations can enhance advertising effectiveness, strengthen brand image, and support the success of digital product marketing amidst the evolving competitive landscape of the creative and technology industries. Novelty: Illustrations play a vital role as advertising media in digital product marketing in the era of information technology.